Cyanobacterial Diazotroph Distributions in the Western South Atlantic - Detoni, Amália Maria Sacilotto; Subramaniam, Ajit; Haley, Sheean T.; Dyhrman, Sonya T.; Calil, Paulo H. R. (Frontiers in Marine Science, 2022)
Inputs of new nitrogen by cyanobacterial diazotrophs are critical to ocean ecosystem structure and function. Relative to other ocean regions, there is a lack of data on the distribution of these microbes in the western South Atlantic. Here, the abundance of six diazotroph phylotypes: Trichodesmium, Crocosphaera, UCYN-A, Richelia associated with Rhizosolenia (Het-1) or Hemiaulus (Het-2), and Calothrix associated with Chaetoceros (Het-3) was measured by quantitative PCR (qPCR) of the nifH gene along a transect extending from the shelf-break to the open ocean along the Vitória-Trindade seamount chain (1200 km). Using nifH gene copies as a proxy for phylotype abundance, Crocosphaera signals were the most abundant, with broad distribution throughout the study region. Trichodesmium signals were the second most abundant, with the greatest numbers confined to the warmer waters closer to the coast, and a significant positive correlation with temperature. The average signals for the host-associated diazotrophs (UCYN-A, Het-1, and Het-2) were consistently lower than for the other phylotypes. These findings expand measurements of cyanobacterial diazotroph distribution in the western South Atlantic and provide a new resource to enhance modeling studies focused on patterns of nitrogen fixation in the global ocean.